2020
DOI: 10.1186/s12887-020-02227-1
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Support Ventilation (PSV) versus Neurally Adjusted Ventilatory Assist (NAVA) in difficult to wean pediatric ARDS patients: a physiologic crossover study

Abstract: Background: Neurally adjusted ventilatory assist (NAVA) is an innovative mode for assisted ventilation that improves patient-ventilator interaction in children. The aim of this study was to assess the effects of patientventilator interaction comparing NAVA with pressure support ventilation (PSV) in patients difficult to wean from mechanical ventilation after moderate pediatric acute respiratory distress syndrome (PARDS). Methods: In this physiological crossover study, 12 patients admitted in the Pediatric Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…[20][21] En un estudio fisiológico de grupos cruzados q u e e x p l o r ó l o s e f e c t o s d e l a N A V A e n comparación con la ventilación con presión de soporte en una población pediátrica con síndrome de dificultad respiratoria aguda moderada y dificultad para la desconexión del respirador se observó que la NAVA redujo significativamente el índice de falta de sincronización, mejoró la sincronía entre el paciente y el respirador y mantuvo la estabilidad hemodinámica. 22 Sin embargo, debido a la inmadurez del sistema nervioso y del centro respiratorio de los recién nacidos prematuros, pueden ocurrir episodios múltiples de apnea, cuya incidencia está estrechamente relacionada con la madurez. En otro estudio, se sugirió que la NAVA no presentaba ninguna ventaja obvia en los recién nacidos prematuros y que no puede usarse en reemplazo de la NCPAP.…”
Section: Discussionunclassified
“…[20][21] En un estudio fisiológico de grupos cruzados q u e e x p l o r ó l o s e f e c t o s d e l a N A V A e n comparación con la ventilación con presión de soporte en una población pediátrica con síndrome de dificultad respiratoria aguda moderada y dificultad para la desconexión del respirador se observó que la NAVA redujo significativamente el índice de falta de sincronización, mejoró la sincronía entre el paciente y el respirador y mantuvo la estabilidad hemodinámica. 22 Sin embargo, debido a la inmadurez del sistema nervioso y del centro respiratorio de los recién nacidos prematuros, pueden ocurrir episodios múltiples de apnea, cuya incidencia está estrechamente relacionada con la madurez. En otro estudio, se sugirió que la NAVA no presentaba ninguna ventaja obvia en los recién nacidos prematuros y que no puede usarse en reemplazo de la NCPAP.…”
Section: Discussionunclassified
“…[20][21] A physiological crossover study exploring the effects of NAVA compared to pressure support ventilation in a pediatric population with moderate acute respiratory distress syndrome presenting difficult weaning from mechanical ventilation found that NAVA significantly reduced the asynchrony index, improved patientventilator synchrony, maintaining hemodynamic stability. 22 However, due to the immature development of the nervous system and respiratory center of premature infants, multiple apneas may occur and the incidence is closely related to maturity. Another study suggested that NAVA has no obvious advantage for premature infants and cannot be used as a substitute for NCPAP.…”
Section: Discussionmentioning
confidence: 99%